2023
DOI: 10.4014/jmb.2304.04020
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota of Pregnant Rats Alleviates Fetal Growth Restriction by Inhibiting the TLR9/MyD88 Pathway

Abstract: Fetal growth restriction (FGR) is a prevalent obstetric condition. This study aimed to investigate the role of Toll-like receptor 9 (TLR9) in regulating the inflammatory response and gut microbiota structure in FGR. An FGR animal model was established in rats, and ODN1668 and hydroxychloroquine (HCQ) were administered. Changes in gut microbiota structure were assessed using 16S rRNA sequencing, and fecal microbiota transplantation (FMT) was conducted. HTR-8/Svneo cells were treated with ODN1668 and HCQ to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In vivo experiment showed that the stimulation of toll-receptor 9 (TLR9) by LPS in FGR pregnant rats was associated with the relative abundances of Prevotellaceae, Streptococcus, Prevotella, and Bacteroides. This was observed through the activation of multiple signaling pathways, such as tumor necrosis factor receptor associated factor 3 (TRAF3), TANK-binding kinase 1 (TBK1), and interferon regulatory factor 3 (IRF3) [62]. Maternal food restriction during pregnancy causes IUGR and reduces the immunotolerant milieu in mouse placenta, which may affect immune tolerance and the immunologic pathways regulating ER stress and autophagy [63].…”
Section: Animal Modelsmentioning
confidence: 99%
“…In vivo experiment showed that the stimulation of toll-receptor 9 (TLR9) by LPS in FGR pregnant rats was associated with the relative abundances of Prevotellaceae, Streptococcus, Prevotella, and Bacteroides. This was observed through the activation of multiple signaling pathways, such as tumor necrosis factor receptor associated factor 3 (TRAF3), TANK-binding kinase 1 (TBK1), and interferon regulatory factor 3 (IRF3) [62]. Maternal food restriction during pregnancy causes IUGR and reduces the immunotolerant milieu in mouse placenta, which may affect immune tolerance and the immunologic pathways regulating ER stress and autophagy [63].…”
Section: Animal Modelsmentioning
confidence: 99%